미숙아 3 세 때의 안과적 고찰 - 최경식; Kyung Seek Choi; 한영근; Young Keun Han; 박성희; Song Hee Park; 신환호; Han Ho Shin (Daihan angwa haghoi jabji, 2000)
미숙아의 경우 만삭아 보다 근시, 사시, 약시 등의 발생빈도가 높으며, 특히 미숙아망막병증이 있었던 경우엔 미숙아망막병증이 없었던 경우 보다 훨씬 많은 안과적 후유증을 갖는다.저자들은 1993년부터 1996년까지 본원 외래를 방문한 만 3세 소아 중 미숙아로 태어나고 미숙아망 막병증이 없었던 31명(62안)과 만삭으로 태어난 31명(62안)에서 안과적 검사를 실시하였다. 나안시력이 0.6 이상인 경우는 미숙아군 27안(43.55%)이었고, 만삭아군 35안(56.45%)이었다. 근시(－0.25디옵터 이상)는 미숙아군 17안(27.42%), 만삭아군 8안(12.9%),원시(2.0디옵터 이상)는 미숙아군 6안(9.68%), 만삭아군 11안(17.74%), 난시(1디옵터 이상)는 미숙아군 21안(33.87%), 만삭아군 10안(16. 13%)이었다. 양안시기능 검사는 티트무스(2 00초 이상), 티엔오(240초 이상)에서 각각 미숙아군 15명(48.4%), 12명(38.7%), 만삭아군 25명(80.6%), 23명(74.2%)이었고 사시는 미숙아군 4명(6.45%)이었고 만삭아군에서는 없었다. 미숙아로 태어난 소아에서는 미숙아망막병증이 없더라도 안과적 이상소견이 만삭아군 보다 많으므로 정기적인 시력, 굴절력, 사시 등의 안과적 검사가 필요하겠다(한안지 41:965~972,2000). The prevalence of myopia, strabismus and amblyopia in premature children is higher than in the full-term population. And the higher incidence of ophthalmic abnormalities was found in the group with retinopathy of prematurity. The authors determined the prevalence of ophthalmic abnormalities in 31 premature children without retinopathy of prematurity com-pared with 31 full-term children. The children were examined when they were 3 years of age from 1993 to 1996. Uncorrected visual acuity of 0.6 or better was noted in 27(43.55%) eyes of the premature children and 35(56.45%) eyes of the full-term children. A total of 17(27.42%) eyes of preterm and 8(12.9%) eyes of full-term children had myopic refractive error(0.25 diopters or greater). And 6(9.68%) eyes of preterm and 11(17.74%) eyes of full-term children had hyperopic refractive error(2.0 diopters or greater). The astigmatism(1.0 diopter or greater)was found in 21(33.87%) eyes in preterm as compared with 10(16.13%)eyes in full-term children. Binocularity was evaluated from Titmus and TNO stereo test. 15(48.4%), 12(38.7%) premature children and 25(80.6%), 23(74.2%) full-term children passed the Titmus 200 seconds of arc and TNO 240 seconds of arc each. Strabismus was not found in full-term children and 4(6.45%) of premature group. Premature infants without retinopathy of prematurity had higher rates of ocular abnormalities than full-term children. The authors conclude that visual development of premature children should be carefully examined including visual acuity, refractive errors, strabismus etc(J Korean Ophthalmol Soc 41:965~972, 2000).